Persistent link between caribbean precipitation and atlantic ocean circulation during the last glacial revealed by a speleothem record from Puerto Rico - Warken, Sophie F.; Vieten, Rolf; Winter, Amos; Spötl, Christoph; Miller, Thomas E.; Jochum, Klaus P.; Schröder-Ritzrau, Andrea; Mangini, Augusto; Scholz, Denis (Paleoceanography and paleoclimatology, 2020)
The sensitivity of tropical Atlantic precipitation patterns to the mean position of the Intertropical Convergence Zone (ITCZ) at different time scales is well-known. However, recent research suggests a more complex behavior of the northern hemispheric tropical rain belt related to the ITCZ in the western tropical Atlantic. Here we present a precisely dated speleothem multi-proxy record from a well-monitored cave in Puerto Rico, covering the period between 46.2 and 15.3 ka. The stable isotope and trace element records document a pronounced response of regional rainfall to abrupt climatic excursions in the North Atlantic across the Last Glacial such as Heinrich stadials and Dansgaard/Oeschger events. The annual to multidecadal resolution of the proxy time series allows substructural investigations of the recorded events. Spectral analysis suggests that multidecadal to centennial variability persisted in the regional hydroclimate mainly during interstadial conditions but also during the Last Glacial Maximum. In particular, we observe a strong agreement between the speleothem proxy data and the strength of the Atlantic meridional overturning circulation, supporting a persistent link of oceanic forcing to regional precipitation. Comparison to other paleo-precipitation records enables the reconstruction of past changes in position, strength, and extent of the ITCZ in the western tropical Atlantic in response to millennial- and orbital-scale global climate change.
First published: 03 November 2020
Gesehen am 12.10.2021